EFFECT OF AUTOGENIC TRAINING ON PAIN REDUCE TO PATIENTS POST FRACTURE OPERATION (Study in Regional hospital. Dr. Sayidiman Magetan) - Wan Yan Prayogi; Sri Sayekti; Anin Wijayanti (Jurnal Keperawatan, 2014)
Problem often encountered on patients post fracture operation is pain. In Indonesia, especially in Magetan, data obtained in Regional hospital. Dr. Sayidiman Magetan was noted that the number of patients who underwent post fracture operation in 2013 from 1st January 2013 to 30th February 2013 were as many as 103 people with a various of fracture cases with the intensity of diferent pain. The purpose of this study was to know the effect of Autogenic training to pain reduce to patients post fracture operation. The study type of research is experimental research with Quasi experiment approach and design used was a pre-experiment (One group pre and post test). its population was all patients post fracture operation in 2014 within a period of 1 month. Sample was 10 patients post fracture operation performed by random sampling technique. Independent variable was Autogenic training and Dependent variable was pain. Instrument used was observation sheet. The data was processed through editing, coding, scoring. To know effect of Autogenic training to pain reduce to patients post fracture operation used Wilcoxon test. Result of Wilcoxon test ρ = 0.007 (ρ <α) showed any effect between Autogenic training with pain reduce to patients post fracture operation. Based on the study result can be concluded that there was effect of Autogenic training to pain reduce to patients post fracture operation in Regional hospital. Dr. Sayidiman Magetan in 2014.Keywords: Auotogenic training, pain, patient post operation